Bandstand, a new musical [compact disc] : original Broadway cast recording - Oberacker, Richard (Broadway Records, 2017)
A swing music-fueled, against-all-odds story comes to life in a musical featuring two-time Tony nominee Laura Osnes, Broadway sensation Corey Cott, and Tony winner Beth Leavel.